Estudio de pre factibilidad para la instalación de un fast food saludable en una zona empresarial de Lima - Castañeda Rubio, Andrea Liliana (2019)
The present work aims to determine the market, technological, economic, financial and social viability for the installation of a healthy fast food service in a business area.